Influence of sediment resuspension on the efficacy of geoengineering materials in the control of internal phosphorous loading from shallow eutrophic lakes. (December 2016) - Yin, Hongbin; Kong, Ming; Han, Meixiang; Fan, Chengxin
Abstract: Modified clay-based solid-phase phosphorous (P) sorbents are increasingly used as lake geoengineering materials for lake eutrophication control. However, some still dispute the feasibility of using these materials to control internal P loading from shallow eutrophic lakes. The lack of information about P behavior while undergoing frequent sediment resuspension greatly inhibits the modified minerals' use. In this study, a sediment resuspension generating system was used to simulate the effect of both moderate winds (5.1 m/s) and strong winds (8.7 m/s) on the stability of sediment treated by two geoengineering materials, Phoslock ® (a lanthanum modified bentonite) and thermally-treated calcium-rich attapulgite. This study also presents an analysis of the P dynamics across the sediment-water interface of two shallow eutrophic lakes. In addition, the effect of wind velocity on P forms and P supply from the treated sediment were studied using chemical extraction and diffusive gradients in thin films (DGT) technique, respectively. Results showed that adding geoengineering materials can enhance the stability of surface sediment and reduce the erosion depth caused by wind accordingly. All treatments can effectively reduce soluble reactive phosphorus (SRP) concentration in overlying water when sediment is capped with thermally-treated calcium-rich attapulgite, which performs better than sediment mixed with modified attapulgite but not as well as sediment treated with Phoslock ® . However, their efficiency decreased with the increase in occurrences of sediment resuspension. The addition of the selected geoengineering materials effectively reduced the P fluxes across sediment-water interface and lowered P supply ability from the treated sediment during sediment resuspension. The reduction of mobile P and enhancement of calcium bound P and residual P fraction in the treated sediment was beneficial to the long-term lake internal P loading management. All of the results indicated that the studied geoengineering materials are suitable for application in shallow eutrophic lakes with frequent sediment resuspension activity. Highlights: Modified clays were used as geo-engineering materials for eutrophication control. Geoengineering material addition can solidify sediment and enhance its stability. Frequent sediment resuspension reduces SRP control efficiency of modified clays. Modified clays decrease sediment P supply and P flux across sediment-water interface. Adding geoengineering materials can transform sediment mobile P into inert P form.